2022
DOI: 10.3390/children9060867
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Continuity of Care in Pediatric Neurology Services during COVID-19 Lockdown: An Additional Stressor for Parents

Abstract: Background. This study aimed to investigate the consequence of the COVID 19-related lockdown on the well-being of children with neurological and neurodevelopmental disorders and the repercussion on parental stress during the period 9 March 2020–3 May 2020. Methods. A web-based survey was shared via mail with the parents of children affected by chronic neurologic disorders and neurodevelopmental disorders in the continuity of care in two Italian tertiary centers, independently by the severity of the diseases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This disagreement could be due to the socio-economic changes that have occurred over the last 20 years and to the different perception of the quality of life of the families [ 28 , 29 ]. Furthermore, in this regard, we should also consider that our study was conducted during the COVID-19 pandemic, and this may have been an additional factor that impacted parental stress [ 30 , 31 , 32 ]. Some recent research showed that the COVID-19 pandemic can be a source of parental stress in parents of children and adolescents with various neuropsychiatric conditions, including epilepsy [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This disagreement could be due to the socio-economic changes that have occurred over the last 20 years and to the different perception of the quality of life of the families [ 28 , 29 ]. Furthermore, in this regard, we should also consider that our study was conducted during the COVID-19 pandemic, and this may have been an additional factor that impacted parental stress [ 30 , 31 , 32 ]. Some recent research showed that the COVID-19 pandemic can be a source of parental stress in parents of children and adolescents with various neuropsychiatric conditions, including epilepsy [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research consistently indicates that parents of children with NDDs frequently report elevated levels of stress, anxiety, sadness, and diminished quality of life in comparison to parents of generally developing children [23,39,[66][67][68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the COVID-19 pandemic has intensified the levels of stress experienced by parents of children with neurodevelopmental disorders (NDDs) due to the loss of continuity of care and the impact on the well-being of children with NDDs [23,72].…”
Section: Discussionmentioning
confidence: 99%
“…The literature highlights that parents or caregivers of children showing higher PSS scores are likely undergo a clinically significant level of parental stress, necessitating referral to professional care services and potential clinical monitoring. 16 The consequences of enduring heightened and/or persistent parental stress can manifest in both short-term and long-term scenarios, commonly linked to adverse effects on psychological wellbeing, overall quality of life, and the availability of social support for parents. 17,18 Elevated parental stress has the potential to negatively impact the quality of parent-child relationships, feelings of competence, and overall parental well-being.…”
Section: Discussionmentioning
confidence: 99%